Choice and rejection of psychiatry as a career: surveys of UK medical graduates from 1974-2009 - Goldacre, M; Fazel, S; Smith, F; Lambert, T (Royal College of Psychiatrists, 2013)
BACKGROUND: Recruitment of adequate numbers of doctors to psychiatry is difficult. AIMS: To report on career choice for psychiatry, comparing intending psychiatrists with doctors who chose other clinical careers. METHOD: Questionnaire studies of all newly qualified doctors from all UK medical schools in 12 qualification years between 1974 and 2009 (33 974 respondent doctors). RESULTS: One, three and five years after graduation, 4-5% of doctors specified psychiatry as their first choice of future career. This was largely unchanged across the 35 years. Comparing intending psychiatrists with doctors who chose other careers, factors with a greater influence on psychiatrists' choice included their experience of the subject at medical school, self-appraisal of their own skills, and inclinations before medical school. In a substudy of doctors who initially considered but then did not pursue specialty choices, 72% of those who did not pursue psychiatry gave 'job content' as their reason compared with 33% of doctors who considered but did not pursue other specialties. Historically, more women than men have chosen psychiatry, but the gap has closed over the past decade. CONCLUSIONS: Junior doctors' views about psychiatry as a possible career range from high levels of enthusiasm to antipathy, and are more polarised than views about other specialties. Shortening of working hours and improvements to working practices in other hospital-based specialties in the UK may have reduced the relative attractiveness of psychiatry to women doctors. The extent to which views of newly qualified doctors about psychiatry can be modified by medical school education, and by greater exposure to psychiatry during student and early postgraduate years, needs investigation.